Magnetic field induced finite size effect in type-II superconductors - Schneider, T. (Физика низких температур, 2006)
We explore the occurrence of a magnetic field induced finite size effect on the specific heat and
correlation lengths of anisotropic type-II superconductors near the zero field transition temperature
Tc. Since near the zero field transition thermal fluctuations are expected to dominate and with
increasing field strength these fluctuations become one dimensional, whereupon the effect of fluctuations
increases, it appears unavoidable to account for thermal fluctuations. Invoking the scaling
theory of critical phenomena it is shown that the specific heat data of nearly optimally doped
YBa₂Cu₃O₇₋δ are inconsistent with the traditional mean-field and lowest Landau level predictions
of a continuous superconductor to normal state transition along an upper critical field
Hс₂(T). On the contrary, we observe agreement with a magnetic field induced finite size effect,
whereupon even the correlation length longitudinal to the applied field H cannot grow beyond the
limiting magnetic length LH ∝ 0/H. It arises because with increasing magnetic field the density
of vortex lines becomes greater, but this cannot continue indefinitely. LH is then roughly set
on the proximity of vortex lines by the overlapping of their cores. Thus, the shift and the rounding
of the specific heat peak in an applied field is traced back to a magnetic field induced finite size effect
in the correlation length longitudinal to the applied field.